Production and characterization of a neutral phytase of Penicillium oxalicum EUFR-3 isolated from Himalayan region - RAMANDEEP KAUR; ABHISHAKE SAXENA; PUNESH SANGWAN; AJAR NATH YADAV; VINOD KUMAR; HARCHARAN SINGH DHALIWAL (Smujo International, 2017)
Kaur R, Saxena A, Sangwan P, Yadav AN, Kumar V, Dhaliwal HC. 2017. Production and characterization of a neutral phytase of Penicillium oxalicum EUFR-3 isolated from Himalayan region. Nusantara Bioscience 9: 68-76. Micronutrient bioavailability from cereals is poor to monogastric animals due to presence of phytate as a chelating agent in seeds and an exogenous application of phytases is required to overcome antinutritional effect of phytate. In the present investigation, 40 fungal isolates including Aspergillus, Penicillium, Trichoderma, Toliposporium, Cladosporium, Talaromyces etc. from different habitats were screened positive for phytase activity on specific media. On the basis of phytase production potential in solid state fermentation conditions, plant epiphytic fungi Penicillium oxalicum strain EUFR-3 has been observed with maximum phytase activity of 12.8 U/g. The biochemical properties i.e. activity and stability under optimum pH and temperature, and effect of modulators on phytase activity from this isolate were studied for its prospective application in human food. The P. oxalicum EUFR-3 phytase (PhyP-EUFR3) had maximum activity at pH 7.0 and temperature 40 Â°C. It was stable in pH range of 3-8 with more than 60 % activity throughout investigation. The thermostability of PhyP-EUFR3 was about 30 % residual activities after 10 min at 80 Â°C. Further purification, characterization and study of catalytic mechanism will be useful in better utilization of this phytase in human food for increased bioavailability of important metal ions.